The lady is a vamp - Storm, Tempest (Atlanta Peachtree Publishers, Ltd., 1987)
This book is a mixture of entertainment, intrique, and inspiration of readers and it will providecompelling evidence of what a woman determined to survive and prosper can do to achieve her goals.
Keywords: Biography